Description of Premarital Sex Knowledge and Behavior in Adolescents in Mosso Village - Izaac, Fransina Alfonsina (Preventif : Jurnal Kesehatan Masyarakat, 2023)
This study aims to describe the knowledge and behavior of premarital sex in teenagers in Mosso Village. This type of research is qualitative with a descriptive approach. The technique in determining informants uses purposive sampling, with criteria that are teenagers who are already dating or are talking at the age of 11-25 years. There were 6 informants on this research. The data collection techniques used are observation and interviews. Data analysis techniques utilized three stages, first stage was data condensation, second stage was data models, and the last was conclusions. The results of this study showed that; teenagers’ knowledge about what premarital sex behavior is lacking. The limited information received by adolescents for taboo reasons is one factor in the lack of information related to the behavior and impact of premarital sex behavior. Information about premarital sex is only heard in church and some information is obtained during school time. What influences the occurrence of premarital sex is; There is a sense of attraction to the opposite sex, the existence of its own lust in adolescents, peer influence and as a means or reason for the adolescent love relationship to be approved by parents and family. Keywords : Knowledge; Behavior; Premarital; Teenager; Mosso